Enhancement of condensation heat transfer on hydrophobic and hydrophilic micro-structured surfaces - Atsushi TOKUNAGA; Takaharu TSURUTA (Nihon Kikai Gakkai ronbunshu, 2018)
It is well known that the dropwise condensation on a hydrophobic surface has a larger heat transfer coefficient than the filmwise condensation. Larger droplets in ordinary systems depart from the condensing surface by the gravity or the shear-force of vapor flow and the bare surface is created for the rapid condensation, resulting in higher heat transfer performance. However, those forces cannot be expected in the micro- and nano-systems because the spaces for the liquid and vapor flow are limited. In order to obtain the larger condensation heat transfer rate, it is necessary to use high heat transfer characteristics of microscopic droplets together with developing a new method for removing the grown droplets from the condensing surface. A challenging work has been carried out in the present paper to remove the droplets effectively, where the micro-scale groove patterns were fabricated with the hydrophobic and hydrophilic surfaces. The experimental results have shown that the condensation heat flux on the micro-structured surface is 1.4 times enhanced compared with the milli-scale structure. For further heat transfer enhancement, improving the drainage ability is required to reduce the condensate flooding.